Interações e viabilidade do plantio consorciado de pinhão-manso (Jatropha curcas) e girassol (Helianthus annuus L.) - Coelho, Ricardo Coeli Simões (2010)
With the recent advent of biodiesel in Brazil, there has been a significant increase in the number of research on the potential of utilizing oleaginous as raw material, especially in physic nut (Jatropha curcas L.), due to its superior oil technical characteristics, as well as the plant s hardiness and productivity. However, since the production of physic nut only becomes economically viable from the third year, there is a need to consider planting in intercropping manner. The aim of this study was to evaluate the interaction and the technical and economical feasibility of intercropping of jatropha and sunflower (Helianthus annuus L.), which is also an excellent source of oil for biodiesel production. The project was implemented at UFSCar / CCA in Araras, São Paulo. The jatropha seedlings were planted in May 1998, spaced 2 meters between plants and 4 meters between rows. The sowing of sunflower variety IAC Iarama was done in November 2008, between physic nut lines, with four rows spaced at fifty centimeters, with an estimated 50,000 seeds per hectare. We evaluated the sunflower plant yield, the development of physic nut and the possible allelopathic interactions between cultures. Allelopathic effects between sunflower and weeds were also investigated. We adopted the split-plot design with four replications and four combinations of consortia, whereas T1: growing sunflowers on both sides of the physic nut planting, T2: growing sunflowers west of the physic nut planting with the east side being reserved for the germination of weeds, T3: growing sunflowers to the east line of physic nut with the west side being reserved for the germination of weeds; T4: both sides of the line of physic nut were reserved for the germination of weeds. It was concluded that there was no influence on the development of jatropha vi ii plantations in intercropped with sunflower and sunflower production was not affected by physic nut. There was also a suppression of spontaneous plants in areas with sunflower. The alternative of this consortium demonstrates a good choice for the national biodiesel program.